2018
DOI: 10.1158/1541-7786.mcr-17-0292
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Phenotypes in Metastatic Melanoma are Governed by SR-BI and its Association with Glycosylation and STAT5 Activation

Abstract: Metastatic melanoma is hallmarked by elevated glycolytic flux and alterations in cholesterol homeostasis. The contribution of cholesterol transporting receptors for the maintenance of a migratory and invasive phenotype is not well defined. Here, the scavenger receptor class B type I (SCARB1/SR-BI), a high-density lipoprotein (HDL) receptor, was identified as an estimator of melanoma progression in patients. We further aimed to identify the SR-BI-controlled gene expression signature and its related cellular phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“… 6 ), colony formation, migration, and invasion of ccRCC cells as well as expression and phosphorylation of Akt ( 6 ). SR-BI has also been associated with carcinogenic features in breast cancer, prostate cancer, and melanoma ( 54 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“… 6 ), colony formation, migration, and invasion of ccRCC cells as well as expression and phosphorylation of Akt ( 6 ). SR-BI has also been associated with carcinogenic features in breast cancer, prostate cancer, and melanoma ( 54 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Folding progress of these N-glycosylated proteins is monitored by UGGT1 that selectively recognizes and reglucosylates misfolded and misassembled glycoproteins (Hebert and Molinari, 2012). Previous study found that SR-BI facilitates STAT5 O-glycosylation (Kinslechner et al, 2018). Interestingly, we found a strong association of UGGT1 and SR-BI, which is unique because that not all N-glycosylated protein strongly interacted with UGGT1.…”
Section: Discussionmentioning
confidence: 98%
“…In line with an oncogenic role, knock down of SR-BI was found to inhibit proliferation (Figure 9, ref (6)), colony formation, migration and invasion of ccRCC cells as well as expression and phosphorylation of Akt (6). SR-BI has also been associated with carcinogenic features in breast cancer, prostate cancer, and melanoma (54,55).…”
Section: Discussionmentioning
confidence: 99%